THE EFFECTS OF ORGANIZATIONAL AND SOCIAL SUPPORT ON EMPLOYEES PSYCHOLOGICAL WELL-BEING - Özyer, Kubilay; Polatci, Sema (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to determine which type of perceived support - organizational or social - makes employees experience greater well-being. Social support may be derived from family, friends, peers, and other personal networks. It differs from organizational support, which involves bosses, managers, co-workers, and trainers or formal mentors. In this study, we determined which type of perceived support is more effective in increasing the psychological well-being of employees. The data were collected from service sector employees. Following an analysis of the collected data, the effects of perceived organizational support and perceived social support on psychological well-being were clarified. The analysis results show that organizational support and social support have no significant effects on employees’ psychological well-being. This point to a result that is contrary to what is reported in the literature. Additionally, several suggestions made to increase employees’ psychological well-being.